Etika Profesi Teknologi Informasi Komunikasi Ditinjau Dari Sudut Pandang Ajaran Islam - Warsino Nardiwiyono; Yahya Mara Ardi (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Science and technology develop significantly. Computer and internet become integral part of this technology development, particularly in information technology. One of the challenges should be faced in this fast development of information technology is ethical issue. This article explains that Islam as comprehensive teachings is able to provide solutions for any problems in relations to ethical issue. Aspects of ethical issue, which consist of privacy, accuracy, property, and accessibility, are entirely contained in the main teaching sources of Islam, namely the Qur'an and Hadith. After reading this article, Muslims as the majority population in Indonesia may be wiser and utilize ethics as part of their worships and obedience to Allah the Great